One man's castle : Clarence Darrow in defense of the American dream - Vine, Phyllis, 1945- (New York : Amistad, 2004)
Publisher's description: This tautly told story steps back to a time when Detroit's boosters described their city as one of the most cosmopolitan in the world. It was also a city in which tensions between blacks and whites seemed manageable. Yet all that changed in 1925, when a black family named Sweet bought and moved into a house in a white neighborhood. What began with mothers bringing their children to gawk and stare soon became an angry mob of men, some of them from the local KKK, with stones. The violence that ensued landed Ossian Sweet, a doctor from the "talented tenth," and others from his family in jail and compelled the NAACP -- which had taken up the Sweets' case -- to hire famed attorney Clarence Darrow, who had just finished defending the plaintiff in Tennessee v. John Scopes. Darrow's defense led to one of the most incendiary courtroom dramas in the history of the United States. The outcome was a triumph of cooperation that transcended race in the name of justice.
Prologue -- Florida: "Incomparable and indescribable" -- The education of Ossian Sweet -- Moving up -- Getting settled -- "Detroit the dynamic" -- Two cities: Vienna and Paris -- 2905 Garland Avenue -- James Weldon Johnson and the NAACP -- Send Walter White -- Clarence Darrow sets the stage -- "Nobody is molesting you" -- Your fight/my fight -- The night of September 9 -- His home is his castle -- A reasonable man? -- More than a partial victory -- A trial fair -- The darker brother -- Epilogue: after the trials.
Map on lining paper.
Includes bibliographical references (pages 273-314) and index.
Keywords: Sweet, Ossian, -- 1895-1960 -- Trials, litigation, etc; Darrow, Clarence, -- 1857-1938.; Darrow, Clarence, -- 1857-1938; Sweet, Ossian, -- 1895-1960; Darrow, Clarence; Trials (Murder) -- Michigan -- Detroit; African Americans -- Civil rights -- History -- 20th century; African Americans -- Civil rights; Trials; Trials (Murder); Michigan -- Detroit; 1900-1999; Trial and arbitral proceedings; History; Trial and arbitral proceedings